Characterization of tryptophan aminotransferase 1 of Malassezia furfur, the key enzyme in the production of indolic compounds by M. furfur. Issue 11 (29th October 2013) - Preuss, Janina; Hort, Wiebke; Lang, Sarah; Netsch, Anette; Rahlfs, Stefan; Lochnit, Günter; Jortzik, Esther; Becker, Katja; Mayser, Peter A.
Abstract: Malassezia yeasts are responsible for the widely distributed skin disease Pityriasis versicolor (PV), which is characterized by a hyper‐ or hypopigmentation of affected skin areas. For Malassezia furfur, it has been shown that pigment production relies on tryptophan metabolism. A tryptophan aminotransferase was found to catalyse the initial catalytic step in pigment formation in the model organism Ustilago maydis . Here, we describe the sequence determination, recombinant production and biochemical characterization of tryptophan aminotransferase MfTam1 from M. furfur . The enzyme catalyses the transamination froml ‐tryptophan to keto acids such as α‐ketoglutarate with K m values for both substrates in the low millimolar range. Furthermore, MfTam1 presents a temperature optimum at 40°C and a pH optimum at 8.0. MfTam1 activity is highly dependent on pyridoxal phosphate (PLP), whereas compounds interfering with PLP, such as cycloserine (CS) and aminooxyacetate, inhibit the MfTam1 reaction. CS is known to reverse hyperpigmentation in PV. Thus, the results of the present study give a deeper insight into the role of MfTam1 in PV pathogenesis and as potential target for the development of novel PV therapeutics.